Central American migration to the United States. a joint research proposal submitted to The Agency for International Developement Department of State. Carlos Federico Denton Lister, Guy Poitras y Alex Allen - Poitras, Guy
Estudio teórico sobre la migración circular centroamericana hacia los Estados Unidos de Norteamérica, y su entorno económico y social